A multi-frequency approach to mitigate the performance degradation of a magnetic positioning system under CW disturbance conditions. (September 2020) - Capriglione, D.; Cerro, G.; Ferrigno, L.; Milano, F.; Moschitta, A.
Highlights: Short Range Magnetic Localization System. Disturbance set-up following IEC/EN 61000-4-6. Noisy Environment Localization System. Disturbance detection and rejection method. Magnetic measurements experimental campaign. Abstract: Magnetic localization in 3D space is a challenging but promising task in those indoor applications where low costs and limited range are key requirements as in industrial and in some medical clinics' frameworks. In such cases, the localization system generally operates in disturbed environments where, in the worst case, continuous-wave disturbances could permanently affect the system performance. Therefore, the evaluation of its susceptibility to external disturbances is an issue to be assessed, before deploying the most suitable solution. Therefore, it is important to accomplish for two tasks: (i) to quantify the disturbance effect on the system performance and (ii) to propose robustness solutions to minimize the disturbance effect, thus allowing the system to behave as in regular mode. In this paper, concerning with continuous wave conducted disturbances, which act as the most impacting external disturbing sources, both the tasks are addressed by considering both analytical modeling and experimental validations.